THE KINETICS AND OXIDATION OF NEUTRAL RED BY ClO₃⁻ IN AN AQUEOUS ACIDIC MEDIUM - Umoru, Patricia Ese; Nkole, Ikeckuwku Ugbaga; Micheal, Joyce Felicity (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2025)
The kinetics and oxidation of neutral red by chlorate ion were studied in an aqueous hydrochloric acid medium at 300 K, with an ionic strength (µ) of 0.2 M (NaCl), by monitoring the absorbance of neutral red (NR) at 515 nm. The reaction was found to be first order concerning both [NR] and [ClO₃⁻], with a stoichiometric mole ratio of 1:1 between NR and ClO₃⁻. The effect of ionic strength variations was further confirmed by observations that the reaction rate was independent of changes in ionic strength and that the addition of cations had no effect on the rate. No evidence of active radical involvement was observed. The experimental rate law determined was: Rate = (Kk₃[H⁺])[NR][ClO₃⁻]. Based on the experimental results, an outer-sphere mechanistic pathway is proposed.